The influence of website quality on purchasing decisions in Lazada e-commerce - Hikmah, Nur Suci; Mavilinda, Hera Febria; Iisnawati (Nur Science Institute, 2024)
The quick development of e-commerce has changed how consumers make purchases, and the quality of a website is a major factor in what people decide to buy online. The purpose of this research is to ascertain how purchase choices made in Lazada e-commerce are influenced by the quality aspects of websites, including usability, information quality, and service interaction quality. This study used a descriptive quantitative methodology. Purposive sampling was used in this research to choose 100 respondents depending on certain criteria. Questionnaires were used in the data collection method. The data analysis method used to test the effect of the three dimensions of website quality on purchasing decisions was multiple linear regression analysis. The results indicate that the usability variable has a partial effect on purchasing decisions. In contrast, the information quality variable and the service interaction variable have no partial effect on purchasing decisions in Lazada e-commerce. Furthermore, the usability, information quality, and service interaction variables in the website quality dimension simultaneously affect purchasing decisions in Lazada e-commerce, with the usability variable being the most dominant factor.